2020
DOI: 10.1186/s13006-020-00284-x
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of the Determinants of Exclusive Breastfeeding (EBF) Practices in Wajir County, Kenya

Abstract: Background: The World Health Organization recommends exclusive breastfeeding for the first six months of life. A qualitative study was conducted to assess the factors that influence the practice of exclusive breastfeeding amongst mothers attending Wajir County Hospital, Kenya. Method: This study was part of a cross-sectional study to compare the exclusive breastfeeding rates amongst primiparous and multiparous mothers with infants under 6 months old attending Wajir County Hospital. Focus group discussions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
8
1
4
Order By: Relevance
“…It has also been well documented that when healthcare personnel provide encouragement and support on breastfeeding to women, the likelihood of initiating and sustaining breastfeeding increases [54,55]. Health providers' supportive influence was positively associated with EBF practice but not early initiation of breastfeeding.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has also been well documented that when healthcare personnel provide encouragement and support on breastfeeding to women, the likelihood of initiating and sustaining breastfeeding increases [54,55]. Health providers' supportive influence was positively associated with EBF practice but not early initiation of breastfeeding.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings are also consistent with previous reviews of randomized controlled trials [56] that showed professional-led support from health providers had a greater impact on the practice of EBF compared to peer-led support. SBC programs need to promote the importance of utilizing health facilities for delivery in the communities and also expand breastfeeding promotion through health providers by specifically targeting women during ANC counseling sessions [55].…”
Section: Discussionmentioning
confidence: 99%
“…A Kenyan study also cited cultural factors such as babies failure to thrive without water, unsupportive mothers in-law, and clan elders threatening to disown mothers who practice EBF. 15 Negative community perception could also be due to the less community sensitization on EBF.…”
Section: Social-cultural Factorsmentioning
confidence: 99%
“…In a study carried out in Rural Kenya, maternal age was associated with breastfeeding practices as mothers of lower age did not practice exclusive breastfeeding (Talbert et al, 2020). Additionally, a study conducted by Mohamed et al (2020) in the North-Eastern region of Kenya indicated that older mothers were more likely to breastfeed. Conversely, younger mothers were more likely to practice exclusive breastfeeding, as Mututho et al (2017)reported in a study conducted in Nairobi.…”
Section: Demographic Factors Associated With Breastfeeding Practicesmentioning
confidence: 99%